USE OF CHEMICAL REAGENTS AGAINST DEHYDROGENASE OF SULFATEREDUCING BACTERIA AT THE NORTH URTABULOK MINE - Rustamov, Mirzokhid (Innovatsion texnologiyalar, 2024)
This article presents the comparative results of determining the effectiveness of three bactericidal reagents with different active bases against sulfate-reducing bacteria (STV) isolated from the water of the North Central oil field. Based on the measurement of the dehydrogenase activity of sulfate-reducing bacteria, the possibility of developing new methods for determining the bactericidal effects of reagents was shown. A method of selecting a chemical reagent that can fight against bacteria by growing them in Rosgate medium is shown. There are many types of sulfatereducing bacteria, and the fight against them requires individual treatment. Therefore, it is necessary to grow the bacteria in the right environment and choose the most suitable reagents. As a result, we also tested eight different chemical reagents against bacteria grown in the right environment and selected the chemical reagent that gave the best results. In the future, it is planned to study the results of using the chemical reagent developed in this laboratory environment in mine conditions